Artificial light at night and risk of depression: a systematic review and meta-analysis - Manman Chen; Yuankai Zhao; Qu Lu; Zichen Ye; Anying Bai; Zhilan Xie; Daqian Zhang; Yu Jiang (Environmental Health and Preventive Medicine)
Background: Artificial light at night (ALAN) has been increasingly recognized as a potential environmental risk factor for mental health issues. However, no meta-analyses have been conducted to summarize the findings. This study aimed to evaluate the pooled associations between outdoor and indoor ALAN exposures and the risk of depression. Methods: Adhering to the PRISMA guideline, we conducted systematic searches across PubMed, Web of Science, EMBASE, Cochrane, and Ovid databases for studies published before May 1st, 2024. Results: A total of 7 studies (5 for outdoor ALAN and 2 for indoor ALAN) with a combined total of 560,219 participants were included in the meta-analysis. Specifically, a 1 nW/cm2/sr increase in outdoor ALAN was associated with a 0.43% (95% CI: 0.21%, 0.65%) increase in depression risk. Meanwhile, a 1 lux increase in indoor ALAN was associated with a 3.29% (95% CI: 0.85%, 5.79%) increase in depression risk. No potential heterogeneity was observed for outdoor ALAN exposure and indoor ALAN exposure. Subgroup analyses for outdoor ALAN indicated that development level, sample size, age group, sex, study design, modality of depression assessment, or adjustment of sleep-related variables in models may not be potential sources of heterogeneity. Sensitivity analyses confirmed the robustness of the findings, while evidence of publication bias was observed for studies on outdoor ALAN. Conclusions: Our findings suggest that both outdoor and indoor ALAN exposures are associated with increased risk of depression. These results underscore the importance of considering outdoor and indoor ALAN in public health strategies aimed at reducing depression risk. Nevertheless, further studies with prospective design are still warranted considering the limited study numbers.